1988
DOI: 10.1172/jci113427
|View full text |Cite
|
Sign up to set email alerts
|

Specific amino acid (L-arginine) requirement for the microbiostatic activity of murine macrophages.

Abstract: The microbiostatic action of macrophages was studied in vitro employing peritoneal cytotoxic macrophages (CM) from mice acting against Cryptococcus neoformans cultured in Dulbecco's medium with 10% dialyzed fetal bovine serum. Fungistasis was measured using electronic particle counting after lysis of macrophages with detergent.Macrophage fungistasis failed in medium lacking only Larginine. Complete fungistasis was restored by L-arginine; restoration was concentration dependent, maximal at 200 MuM. Deletion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
169
1
3

Year Published

1989
1989
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 321 publications
(185 citation statements)
references
References 33 publications
(24 reference statements)
9
169
1
3
Order By: Relevance
“…The role of NO production by macrophages during the phagocytosis of IC has mainly been associated with the cytotoxic activity of these cells for killing ingested or attached microbes (9,10). In fact, Fc␥R-mediated engulfment by macrophages has been consistently studied by first priming the macrophages with pro-inflammatory cytokines, which results in strong activation and secretion of high levels of NO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of NO production by macrophages during the phagocytosis of IC has mainly been associated with the cytotoxic activity of these cells for killing ingested or attached microbes (9,10). In fact, Fc␥R-mediated engulfment by macrophages has been consistently studied by first priming the macrophages with pro-inflammatory cytokines, which results in strong activation and secretion of high levels of NO.…”
Section: Discussionmentioning
confidence: 99%
“…Secretion of NO during Fc␥R engagement has conventionally been measured only when the macrophages are first primed with lipopolysaccharide (LPS) or cytokines such as IFN␥ and/or TNF␣ (6 -8). This results in high-output NO that can exert cytotoxic effects on a variety of pathogens, including bacteria, viruses, fungi, and parasites (9,10). However, the generation of low output NO by macrophages is emerging as an important event in the initiation or modulation of inflammatory responses.…”
mentioning
confidence: 99%
“…Nitrite/nitrate synthesis occurs in vivo in mice during mycobacterial infection (7). Inhibition of the facultative intracellular pathogen, Cryptococcus neoformans, by macrophages in vitro depends upon the concentration of L-arginine available, in the extracellular environment, within the physiologic range (8). These findings implicate metabolism ofL-arginine by macrophages as a possible biochemical pathway for establishing and maintaining microbial dormancy.…”
Section: Introductionmentioning
confidence: 98%
“…Cell-mediated immunity plays a major role in host defense (3)(4)(5)(6)(7), and Th1 cytokines, such as IFN-␥, which acts by inducing NO-dependent fungicidal activity of macrophages (8,9), are essential for this response (10). Many investigators have reported the essential role of IL-12, an important cytokine for differentiation of Th1 cells (11), in host resistance to a variety of infectious pathogens (12)(13)(14)(15)(16)(17).…”
mentioning
confidence: 99%